Религиозные обряды и празднества в общественной жизни античных городов Северного Причерноморья - Ручинская, О.А. (Харківське історико-археологічне товариство, 1994)
The different rites were the characteristicele of the ancient Greek religion. The existence of these sacred acts in the nothern part of the Black Sea coast proved by some archaeological, epigraphic and numismatic evidences. The citizens were taking an active part in sacrifices, public meals and prayers, religious festivals. The latter were the most interesting reflection of the ancient social life there. There were festivals which were dedicated to such Gods as Apollo, Hermes, Heracles, Ahillius, Dionisus, Virgin. There is good evidence that in the autonomous period the religious festivals had a great socil resonance. Later, in the period of the Roman influence, they became entertainments than sacred rites and gradually lost their social significance.
Keywords: Северное Причерноморье; античность; религиозный обряд; религиозное празднество; общественная жизнь